Study on dynamic strength and liquefaction mechanism of silt soil in Castor earthquake prone areas under different consolidation ratios - Chunlin, Jiang; Guangjin, Wang; Shujian, Li; Fuqi, Kang; Binting, Cai; Lei, Zhao (Frontiers in Earth Science, 2023)
Under the Castor earthquake, there is a risk of liquefaction instability of saturated tailings, and the evolution of dynamic pore pressure can indirectly reflect its instability process. Before applying dynamic loads, the static stress state of soil is one of the main factors affecting the development of soil dynamic strength and dynamic pore pressure, and there are significant differences in soil dynamic strength under different consolidation ratios. This paper conducted dynamic triaxial tests on saturated tailings silt with different consolidation ratios, and analyzed the dynamic strength variation and liquefaction mechanism of the samples using the discrete element method (PFC3D). The results showed that 1) as the Kc′ gradually increased, and there was a critical consolidation ratio Kc′ during the development of the dynamic strength of the sample. The specific value of Kc′ was related to the properties and stress state of saturated sand. The Kc′ in this research was about 1.9. When Kc < 1.9, dynamic strength was increased with the increase in Kc; when Kc > 1.9, dynamic strength was decreased with the Kc. 2) Under the impact of cyclic load, when samples were normally consolidated (Kc =1), the pore water pressure would tend to be equal to the confining pressure to cause soil liquefaction. In the case of eccentric consolidation (Kc > 1), the pore water pressure would be less than the confining pressure, thus, the soil liquefaction would not be induced, and the pore pressure value would decrease with the increase of consolidation ratio. This paper provides engineering guidance value for the study of dynamic strength and liquefaction mechanism of tailings sand and silt in Castor earthquake prone areas under different consolidation ratios.